Statistical classification of ultrasonic image texture - DaPonte, John S.; Gelber, Joel; Fox, Martin D. (Publ by IEEE, 1989)
Qualitative analysis is important because it is not subjective and does not have the potential for variation from one observer to another. A description is given of how statistical hypothesis testing can be used to select the quantitative descriptors best capable of distinguishing between normal and abnormal liver texture. Information is also presented on how both parametric and nonparametric discriminant analysis can be applied to determine how well the quantitative analysis compares with the qualitative diagnosis supplied for each case studied.
Keywords: Acoustic Imaging--Digital Techniques; Biomedical Engineering; Liver Disease Diagnosis; Quantitative Descriptor Selection; Statistical Classification Techniques; Statistical Hypothesis Testing; Statistical Methods--Statistical Tests; Ultrasonic Devices--Medical Applications; Ultrasonic Image Texture Classification; dept.csc; ⛔ No DOI found